2021
DOI: 10.1109/tpami.2021.3054719
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task Learning for Dense Prediction Tasks: A Survey

Abstract: With the advent of deep learning, many dense prediction tasks, i.e. tasks that produce pixel-level predictions, have seen significant performance improvements. The typical approach is to learn these tasks in isolation, that is, a separate neural network is trained for each individual task. Yet, recent multi-task learning (MTL) techniques have shown promising results w.r.t. performance, computations and/or memory footprint, by jointly tackling multiple tasks through a learned shared representation. In this surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
257
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 433 publications
(258 citation statements)
references
References 77 publications
0
257
1
Order By: Relevance
“…During the training process, the decreasing rate of L c , L d , L s , L p , and L r may be inconsistent, causing the model to be dominated by a certain module [14]. Hence, need to use weight coefficients, for the entire network, the final loss function is given by…”
Section: Classification Lossmentioning
confidence: 99%
“…During the training process, the decreasing rate of L c , L d , L s , L p , and L r may be inconsistent, causing the model to be dominated by a certain module [14]. Hence, need to use weight coefficients, for the entire network, the final loss function is given by…”
Section: Classification Lossmentioning
confidence: 99%
“…It achieves this by utilizing encoder-level interactions to generate a shared representation [22,9,17], by using decoder-level interactions to improve single task results from multi-modal distillation [35,38], or a set combination of both. [32] shows that in an MTL setting, performance strongly varies depending on a wide range of parameters (e.g task type, label source) and thus architecture and optimization strategies must be selected on a per case basis. In general it is observed that encoder level interactions perform well for multiple classification problems while decoder level interactions have an advantage in dense prediction tasks.…”
Section: Related Workmentioning
confidence: 99%
“…The surrounding area of each point is discretized into a set number of bins. This allows us to restate the problem of the bounding box center localization on the transverse plane (x, z) as a classification problem which are shown to be better fitted for encoder-focused architectures [32]. To achieve finer details, we allow a residual to be regressed for each bin.…”
Section: Joint Proposal Generation and Point Cloud Semantic Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Multitask learning (MTL) deep neural networks are widely used in many fields [26,[33][34][35][36]. It would be an intuitive and promising idea to concurrently solve the AMR and MPE tasks together in an MTL way.…”
Section: Introductionmentioning
confidence: 99%